Multivalent Glyconanoparticles with Enhanced Affinity to the Anti-Viral Lectin Cyanovirin-N - Wang, Xin (2011)
Low-mannose (LM) structures were coupled to gold nanoparticles (Au NPs) to amplify the affinity of LMs with Cyanovirin-N (CV-N) lectins and to study the structures of CV-N variants CVN(Q50C) and CVN(MutDB).